COMPARATIVE ANALYSIS OF FOSTER CARE FOR ADULTS IN REPUBLIC OF CROATIA AND REPUBLIC OF MACEDONIA - Laklija, Maja; Ilievski, Vladimir (Ревија за социјална политика/Journal of Social Policy, 2015)
The aim of this work is to show practice and opportunities forimprovement of foster care for adults in Republic of Croatia and Republicof Macedonia, through a comparative analysis of the legal frameworkgoverning foster care. The analysis will focus on the comparison ofcertain statutory provisions that are related to foster care and state themain differences that exist in these countries. We will analyze theprovisions relating to the types of foster care present in those countries,the accommodation capacities, the conditions to be met to perform fosteractivities, training and education of foster careers, the issuance of alicense to conduct foster care and issues related with conclusion of thecontract and compensation for foster carers. We will also display statisticsabout the current situation on the field of foster care in each country andpropose guidelines for the further development of foster care for adults inCroatia and Macedonia.